2014
DOI: 10.1073/pnas.1310442111
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nonlinearity explains greater visual spatial resolution for darks than lights

Abstract: Astronomers and physicists noticed centuries ago that visual spatial resolution is higher for dark than light stimuli, but the neuronal mechanisms for this perceptual asymmetry remain unknown. Here we demonstrate that the asymmetry is caused by a neuronal nonlinearity in the early visual pathway. We show that neurons driven by darks (OFF neurons) increase their responses roughly linearly with luminance decrements, independent of the background luminance. However, neurons driven by lights (ON neurons) saturate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
229
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(272 citation statements)
references
References 39 publications
35
229
3
Order By: Relevance
“…Recent accumulated evidence indicates that neurons in V1 are more sensitive to black than to white stimuli (Jin et al, 2008;Yeh et al, 2009;Xing et al, 2010;Kremkow et al, 2014). Our data support these findings and further show the spatial characteristics of the black/white differences: a strong difference at the squares' center and a weaker difference at the edges.…”
Section: Black Versus Whitesupporting
confidence: 89%
See 3 more Smart Citations
“…Recent accumulated evidence indicates that neurons in V1 are more sensitive to black than to white stimuli (Jin et al, 2008;Yeh et al, 2009;Xing et al, 2010;Kremkow et al, 2014). Our data support these findings and further show the spatial characteristics of the black/white differences: a strong difference at the squares' center and a weaker difference at the edges.…”
Section: Black Versus Whitesupporting
confidence: 89%
“…More recent neurophysiological studies of single-cell activity in nonhuman primates (Yeh et al, 2009;Xing et al, 2010) found that layer 2/3 neurons responded better to small, localized black spots than to white spots, and also that neurons preferring black outnumbered neurons preferring white stimuli. Others also have observed larger black responses in V1 (Jin et al, 2008;Kremkow et al, 2014). The physiological data on blackwhite preferences are consistent with data from human perceptual experiments (Chubb and Nam, 2000;Chubb et al, 2004).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…So, under selection pressures, adaptation to prevailing conditions (Darwin, 1859) characteristically improves efficiency and performance of living systems (see also de Polavieja, 2004;Pérez-Escudero et al, 2009). Recent studies indicate that natural light environment is asymmetrical, containing more dark than light patches (Ratliff et al, 2010) and that this affects how retinae and brains of animals have adapted to represent the world neurally (Ratliff et al, 2010; Kremkow et al, 2014). In this work, we presented evidence that information sampling in fly photoreceptors may already use this asymmetry to accentuate responses to naturalistic light stimuli, improving vision and likely the flies' fitness.…”
Section: Discussionmentioning
confidence: 57%